Pengaruh Profitabilitas, Kebijakan Dividen, dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Indeks LQ45 di Bursa Efek Indonesia Tahun 2023 - Rambe, Aqli Nadzhari; Imsar, Imsar (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study investigates the effect of profitability, dividend policy, and firm size on firm value among companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) in 2023. The research addresses the issue that firm value, as a key indicator of shareholder wealth, is influenced by various internal factors, yet prior studies have shown inconsistent findings regarding these relationships. Using a quantitative approach, the study employs secondary data from annual financial reports of 45 companies selected through purposive sampling. The variables are measured using Return on Equity (ROE) for profitability, Dividend Payout Ratio (DPR) for dividend policy, firm size (log of total assets), and Tobin’s Q for firm value. Data were analyzed through descriptive statistics and multiple linear regression with a cross-sectional design, using SPSS version 26. The results reveal that profitability has a significant positive effect on firm value (? = 4.807, p < 0.001), indicating that higher profitability reflects better managerial performance and strengthens investor perception. Dividend policy (? = 0.005, p = 0.506) and firm size (? = -6.965E-16, p = 0.390) show no significant effects. However, jointly, the three variables significantly influence firm value (F = 7.876, p < 0.001) with an Adjusted R² of 0.319. These findings imply that while profitability remains a strong driver of firm value in LQ45 companies, dividend policy and firm size alone are less determinant, highlighting the need for investors to evaluate companies holistically.